On the Legislative Developments in Forensic Activity - N. V. Mikhaleva (Теория и практика судебной экспертизы)
The article gives a detailed analysis of the changes made by the Federal Law of 26.07.2019 No. 224-FZ to the Federal Law “On the state forensic activity in the Russian Federation” and the Federal Law “On the Investigative Committee of the Russian Federation”. These developments, primarily related to the establishment of a forensic institution of the Investigative Committee, have been criticized by the legal community since they legalize the supremacy of a criminal prosecution body over the expert offices. At that, some authors justify the need for the forensic expert departments in the structure of the Investigative Committee of the Russian Federation, especially since both in Russia and abroad forensic offices in the bodies dealing with investigating crimes do exist. The Federal Law of 26.07.2019 No. 224-FZ came into force, and till 01.01.2022, the forensic institution of the Investigative Committee of the Russian Federation is to be established, and the list of departmental forensic agencies will be extended.